2019
DOI: 10.3389/fpls.2019.00136
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis, Metabolism and Function of Auxin, Salicylic Acid and Melatonin in Climacteric and Non-climacteric Fruits

Abstract: Climacteric and non-climacteric fruits are differentiated by the ripening process, in particular by the involvement of ethylene, high respiration rates and the nature of the process, being autocatalytic or not, respectively. Here, we focus on the biosynthesis, metabolism and function of three compounds (auxin, salicylic acid and melatonin) sharing not only a common precursor (chorismate), but also regulatory functions in plants, and therefore in fruits. Aside from describing their biosynthesis in plants, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 124 publications
4
51
0
Order By: Relevance
“…Similarly, Sarrou et al 57 also observed that melatonin treated lemon balm (Melissa officinalis) reported an increase in several compounds, in particular nerol, a result similar to our study. Although the role of melatonin in the biosynthesis of essential oil in medicinal plants has not been well understood, one of the mechanisms proposed is related to the similarity in plant function and chemical structure between indole-3-acetic acid (IAA) and melatonin 20,24,28 , which are both derived from chorismate 28 . It has been reported that IAA promotes essential oil synthesis in several medicinal plants 58,59 , and given that melatonin has an auxin-like (IAA) activity, it would be expected that melatonin also promotes the synthesis of essential oils.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Sarrou et al 57 also observed that melatonin treated lemon balm (Melissa officinalis) reported an increase in several compounds, in particular nerol, a result similar to our study. Although the role of melatonin in the biosynthesis of essential oil in medicinal plants has not been well understood, one of the mechanisms proposed is related to the similarity in plant function and chemical structure between indole-3-acetic acid (IAA) and melatonin 20,24,28 , which are both derived from chorismate 28 . It has been reported that IAA promotes essential oil synthesis in several medicinal plants 58,59 , and given that melatonin has an auxin-like (IAA) activity, it would be expected that melatonin also promotes the synthesis of essential oils.…”
Section: Resultsmentioning
confidence: 99%
“…Its ability to protection against abiotic and biotic stresses, in particular low temperature 22 , drought 23,24 , UV-B 25 and heavy metal pollution 26 has also been documented. Many investigations have indicated that melatonin could be considered a plant growth regulator, with a mode of action that works in conjunction with other chorismate-derived phytohormones, including indole-3-acetic acid (IAA) 27 and salicylic acid 28 . Melatonin has a pivotal role in the activation of the antioxidant system and induces changes in gene expression of several physiological mechanisms 21,29 .…”
mentioning
confidence: 99%
“…are known to be the main pathogens affecting cherry fruits ( Habib et al, 2015 ; Chockchaisawasdee et al, 2016 ), very little is still known on how endogenous phytohormone contents might influence their decay. Sweet cherry is a non-climacteric fruit, which is characterized, in contrast to climacteric fruits, by a progressive abscisic acid (ABA) accumulation, a lower respiration rate and almost no ethylene release during ripening ( Pérez-Llorca et al, 2019 ). However, although cherry fruits are composed by an outer layer, the exocarp, an edible mesocarp, and a stony endocarp, no studies have focused thus far on better understanding the contribution of these tissues on fruit decay.…”
Section: Introductionmentioning
confidence: 99%
“…Chorismate is responsible for aromatic amino acids including tryptophan, and through several steps, it can generate the IAA. Meanwhile, chorismate can be converted into isochorismate which transformed into SA (Pérez-Llorca et al 2019).…”
Section: Introductionmentioning
confidence: 99%